2014
DOI: 10.1021/nl500026j
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Organic Nanowires for High Power Density Lithium Ion Batteries

Abstract: The electroactive organic materials are promising alternatives to inorganic electrode materials for the new generation of green Li-ion batteries due to their sustainability, environmental benignity, and low cost. Croconic acid disodium salt (CADS) was used as Li-ion battery electrode, and CADS organic wires with different diameters were fabricated through a facile synthetic route using antisolvent crystallization method to overcome the challenges of low electronic conductivity of CADS and lithiation induced st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
184
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(188 citation statements)
references
References 33 publications
4
184
0
Order By: Relevance
“…Much attention has been paid to the search for electrode materials with low cost, high reversible capacity, and outstanding electrochemical/thermal performance [6,7]. In contrast with inorganic electrode materials, many organic materials have low-cost and renewable characteristics [8][9][10][11] and can be prepared from natural sources.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been paid to the search for electrode materials with low cost, high reversible capacity, and outstanding electrochemical/thermal performance [6,7]. In contrast with inorganic electrode materials, many organic materials have low-cost and renewable characteristics [8][9][10][11] and can be prepared from natural sources.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on these compounds have shown promising electrochemical properties with high energy densities [10][11][12][13] . Recent efforts have enabled the carbonyl-based organic electrodes to have high power as well as stable cycling performance, hinting at a practical feasibility for a bio-inspired design of energy storage materials 10,[14][15][16][17] .…”
mentioning
confidence: 99%
“…1a) have very low solubility in organic electrolyte solvents, and this would result in the excellent stability of these salts as electrode materials. The lithium salt or sodium salt of carbonyl compounds is an effective way to enhance the cycle stability [21,22]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various methods to address these problems, the lithiation of organic molecules is an effective method for inhibiting the dissolution of organic electrode materials in electrolytes [21][22][23][24][25], along with doping a large number of conductive agents [26,27] or using large ring conjugated systems [28][29][30] to increase the electrical conductivity. However, in addition to the two important indicators of conductivity and solubility, the storage, sustainability, and cost of electrode materials for lithiumion batteries are also important parameters influencing their application prospects.…”
Section: Introductionmentioning
confidence: 99%